Effectiveness of Local Revenue and Balance Funds on Capital Expenditure in Indonesian Local Government - Putri, Nucke Febriana; Indriani, Rini; Rahmadini, Dita (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2024)
Local revenues are revenues obtained by regions based on local regulations to finance regional expenditures, and balancing funds are sources of regional income received from the central government for equitable distribution of regional development in the context of implementing regional autonomy to achieve the objectives of granting autonomy to the regions. The purpose of this study is to determine the effect of regional own-source revenue and equalization funds partially on capital expenditures in provinces in Indonesia in 2020-2022. In this research, the author uses agency theory which outlines this theory provides a disclosure. This research uses a survey approach with a quantitative method research type. The data collection technique uses secondary data with secondary data documentation instruments. The population in this study are 34 provinces in Indonesia in 2020-2022 which will be sampled. The data is processed using the panel data regression statistical method. The results showed that local own-source revenue and equalization funds had a positive and significant effect on capital expenditures in provinces in Indonesia. This indicates that local own-source revenues and equalization funds, which are the largest part of regional revenues, are very capable of influencing the allocation of capital expenditures.